A new species of Pterygodermatites (Spirurida: Rictulariidae) in Marmosa constantiae Thomas, 1904 from an ecotone area of the biomes Cerrado/Amazon in the Mato Grosso State, Brazil - Andrade-Silva, Beatriz Elise de; Costa, Natália Alves; Pacheco, Richard de Campos; Rossi, Rogério Vieira; Maldonado, Arnaldo Junior (Frontiers in Veterinary Science, 2022)
A new species of nematode, Pterygodermatites (Paucipectines) sinopiensis n. sp. is described based on specimens recovered from the intestine of the white-bellied woolly mice opossum, Marmosa constantiae trapped in the municipality of Sinop, Mato Grosso state, Brazil. The genus Pterygodermatites has 21 species described in mammals worldwide, and to date, only two species have been described for marsupials in Brazil. The new species is characterized by the presence of 23 small denticles and by the presence of 38-40 and 65 pairs of cuticular processes in males and females, respectively. Additionally, males possess three ventral precloacal fans, and in females, the cuticular processes are divided into 41 pairs of comb-like and 24 pairs of spine-like processes; the vulva opens approximately in pair 41. This study describes the parasite species fifth of marsupials in the Neotropical region.